LITERATURE REVIEW PACLOBUTRAZOL POTENTIAL AND PHYSIOLOGICAL ROLE IN TUBER CROPS AS FOOD DIVERSIFICATION - Anisah, Siti Nur (Universitas Galuh, 2025)
Tuber as one of the vegetative organs of plants, can be utilized as a complementary food or a substitute for rice. Tuber productivity depends on the amount and rate of assimilation, so growth regulators are needed that can increase the productivity of tuberous plants, such as paclobutrazol. Paclobutrazol is a growth regulator that has a major role in inhibiting the vegetative phase of plants. Paclobutrazol will inhibit the rate of gibberellin biosynthesis thus inhibiting plant height growth. Paclobutrazol, containing triazoles, boosts cytokinin biosynthesis, supporting chloroplast separation and chlorophyll biosynthesis whereas anticipating debasement. This comes about in delayed photosynthetic action, expanding acclimatize aggregation for tuber arrangement. At ideal measurements, paclobutrazol keeps up shoot biomass, chlorophyll substance, morphogenesis, photosynthetic capacity, and phytohormone adjust, driving to physiological and morphological changes in plants.